Biological decomposition of detergent active substance in lake waters - Pehlivan, D.; Ozcelik, S.; Yoruk, S. (My University, 1993)
Biological decompositions in the Keban Dam and Hazar Lake water samples of linear alkyl benzene sulfonates (LABS) and branched alkyl benzene sulfonates (DABS) were investigated. As expected, decompositions of DABS were found to proceed very slowly. Decomposition rates of LABs were found to depend on contamination levels of the waters and could be explained by first order rate equations in the concentration range used. -English summary
Deterjan aktif maddesinin gol sularinda biyolojik parcalanmasi
Keywords: Hazar Lake; Keban Dam; Turkey; biodegradation; detergent; lake water quality; reservoir water quality